PENINGKATAN KESIAPTERAPAN TEKNOLOGI PENGOLAHAN SELAI NANAS GAMBUT PADA KELOMPOK USAHA PUAK MILENIAL DI KOTA DUMAI - Sisca Vaulina; Rose Abdullah; Ujang Paman Ismail; Mardaleni Mardaleni; Elinur Elinur; Heriyanto Heriyanto; Nadya Agoestien Siregar; Adelina Br Tarigan; Prayit Subekti; Salam Maulana; Juanda Sinaga (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
Teluk Makmur Village, Medang Kampai District, Dumai City, is one of the peatland pineapple production centers with considerable potential to be developed into value-added processed products. However, pineapple processing by community business groups is still carried out manually using simple household equipment, resulting in low production efficiency and inconsistent product quality. This community service activity aimed to improve the technology readiness of peatland pineapple jam processing at the Puak Milenial Business Group in Dumai City by applying appropriate technology. The methods included identifying initial production conditions, implementing appropriate technologies such as pineapple peeling knives, pineapple grating machines, and stainless-steel jam stirrer machines, and providing technical assistance during the production process. The evaluation used a descriptive-comparative approach, comparing the production system before and after technological intervention. The results showed that the application of appropriate technology improved operational readiness of production by shifting the production system from a manual to a more structured, semi-standardized system at the household industry scale. In addition to improving production efficiency, the use of more hygienic equipment also supported better food production practices. This activity indicates that the application of appropriate technology can be an effective strategy to strengthen the technical capacity of local potential-based MSMEs.